Evaluasi Kondisi Termal Menggunakan Parameter Suhu, Kelembapan Relatif, dan Kecepatan Udara dalam Ruang Aula Masjid At-Taqwa Universitas Muhammadiyah Semarang - Mellisa Putri Syah; Mohhamad Kusyanto (Department of Architecture, Faculty of Engineering and Computer Science, Universitas Muhammadiyah Semarang, 2025)
Thermal comfort is an important factor in the design of a mosque hall used by many congregants for long periods of time. The At-Taqwa Mosque hall of Universitas Muhammadiyah Semarang is frequently used for various activities, but its thermal condition has never been evaluated. This study aims to evaluate the hall's thermal condition based on parameters of air temperature, relative humidity, and air velocity. The method used is a descriptive quantitative approach. Data collection was carried out by measuring temperature, humidity, and air velocity directly at five points from 06.00–18.00 WIB. Analysis was carried out by comparing the results with thermal comfort standards in humid tropical climates (ASHRAE 55 and SNI 03-6572-2001). The results showed a temperature range of 26.4°C–29,9°C and a relative humidity of 76.8%–88.5%. Wind speed ranged from 0.15–0.5 meters/second. The measurement results showed that the air temperature experienced a gradual increase from an average of 26.4°C in the morning to a peak of 29,9°C during the day. Relative humidity showed a decreasing trend from an initial value of 88.5% to as low as 76.8% and increased towards the afternoon, in line with the increase in temperature. Air velocity increased from 0.15 meters/second to a maximum of 0.5 meters/second at midday. These findings emphasize the importance of planning a strategy for managing air temperature, relative humidity, and air velocity parameters in achieving thermal comfort in a room. Optimization strategies for air circulation and natural ventilation management in closed spaces with passive and active ventilation system designs for tropical public spaces to support comfort, energy efficiency, and environmental health in the context of worship. The conclusion is that the mosque hall has the potential for thermal discomfort, so passive design improvements such as cross ventilation and shading are needed.